Stereological examination of the effect on the hippocampal dentate gyrus granule cells number of rats subjected to wireless internet during prenatal period: A preliminary study - Özalper, Büşranur; Rağbetlı, M.Ç.; Çakir, T. (Ondokuz Mayis Universitesi, 2022)
As a result of industrialisation and the many recent advances in technology, we are being intensely subjected to non-ionised radiation sources. As such, the effect of non-ionised radiation on human tissue is now being researched. In this study, the effects of Wi-Fi waves found in some third-generation mobile phones to facilitate internet connection on the brain hippocampal dentate gyrus granule cell quantity of rats during the prenatal period was stereologically examined. During the study, mated albino rats were subjected to Wi-Fi throughout pregnancy. A month after giving birth, six rats from each group, for a total of 12 rats, was sacrificed under perfusion and anaesthesia. Their skulls were opened and brains were removed to undergo routine checks in which the granule cells were counted. Strategic sections were defined, and every 45th section couple (with a thickness of 5 µm) was taken and dyed with haematoxylin and eosin (H&E) and cresyl violet stain. The granule cells were counted using a combination of the stereological disector method and Cavalieri’s principle. Then, the results were analysed using the Mann–Whitney U test. No statistically significant difference has been observed between the groups (p > 0.05). The findings were discussed in light of the relevant literature, and it was determined that throughout pregnancy, Wi-Fi modem device did not result in any changes in the dentate gyrus granule cell count of the hippocampus of postnatal rats’ brains. © 2022 Ondokuz Mayis Universitesi. All rights reserved.
Keywords: number of granule cells; pregnancy; prenatal rat; stereology; wi-fi; eosin; hematoxylin; heparin; ketamine; xylene; albino rat; animal cell; animal experiment; animal tissue; Article; brain stem; brain weight; cell count; controlled study; dentate gyrus granular layer; female; follow up; hippocampus; Internet; male; nonhuman; preliminary data; prenatal period; rat; stereology; wireless communication